1957
DOI: 10.2105/ajph.47.7.856
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Medical Care in Hospitals

Abstract: This study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1963
1963
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…Goldman 8 conducted a review of 12 studies published between the years 1959-1991. 4,[9][10][11][12][13][14][15][16][17][18][19] We extended and updated that review and sought to introduce a taxonomical layer by examining different types of quality measurement with respect to what is being assessed and how it is being assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Goldman 8 conducted a review of 12 studies published between the years 1959-1991. 4,[9][10][11][12][13][14][15][16][17][18][19] We extended and updated that review and sought to introduce a taxonomical layer by examining different types of quality measurement with respect to what is being assessed and how it is being assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Although deficiencies were found at some public clinics, it is not easy to separate poor record-keeping from actual problems in the quality of care. However, in a classic study using hospital records, Rosenfeld (1957) showed that poor recording was also related to substantive shortfalls in quality of care. At public clinics, workers can be trained and supervised to keep standardized records for diarrhea and respiratory infection treatment, making a record audit more productive.…”
Section: Discussionmentioning
confidence: 99%
“…Codman's idea fell into disuse until the mid-1950's, when Lembke (9) and others (14,15), began to use consistent criteria to measure quality of care as reflected in the medical record. These studies reaffirmed the fact that the existence of a record that can be audited can improve medical care.…”
Section: Discussionmentioning
confidence: 99%